Compliance: a perspective from the Brazilian law nº 12.846/2013 - Pereira Ribeiro, Marcia Carla (Universidad Nacional del Litoral, 2015)
This article is intended to reveal a view of the Compliance in business based on economic analysis of law, especially through the notion of the transaction costs and efficiency. It also is intended to demonstrate that the effective implementation of this policy is possible only through mutual cooperation, the only instrument capable of changing the mentality of the players involved and fully execute the development of society. Finally, it examines in particular the structure of incentives created by the Law nº 12.846/2013 (Corporate Anti-Corruption Act), which aims to stimulate the implementation of ethical business conduct, in the fight against corruption, as well as the growth and development of Compliance Programs in Brazil.